St. Lucia : 2008 Article IV Consultation; Staff Report; Staff Supplement, and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2008)
St. Lucia's 2008 Article IV Consultation underlies that progress has been made in reducing fiscal imbalances, yet public debt and debt servicing payments continue to rise. Tourism accounts for more than three-fourths of exports, and the import content of both consumption and foreign direct investment is high. Although the share of value added from the traditionally dominant agriculture sector has declined sharply in recent decades, crop exports support the incomes of much of the country's large rural population.